Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

ZnO-beta zeolite: as an effective and eco-friendly heterogeneous catalyst for the synthesis of benzothiazole derivatives - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Vidhate, Kaluram N.; Lande, Machhindra K. (Chinese Chemical Letters, 2010)
A cheap and recyclable ZnO-beta zeolite was used as catalyst for the synthesis of benzothiazole derivatives. This method provides several advantages such as environmental friendliness, short reaction times, high yields, simple work-up procedure and catalyst was successfully reused for four cycles without significant loss of activity. (C) 2009 Machhindra K. Lande. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Benzothiazole; cyclocondensation; heterogeneous catalyst; ZnO-beta zeolite

ZnO-beta zeolite: as an effective and reusable heterogeneous catalyst for the one-pot synthesis of polyhydroquinolines - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Green Chemistry Letters and Reviews, 2010)
ZnO-beta zeolite, an inexpensive and mild catalyst, has been used for the synthesis of polyhydroquinolines in excellent yields from the one-pot four-component condensation of aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate in ethanol at room temperature. The remarkable advantages offered by this method are a green catalyst, mild reaction conditions, simple work-up procedures, much faster reactions, and excellent yield of products. Furthermore, the catalyst could be reused several times keeping its initial activity in recycled reactions.
Keywords: Hantzsch condensation; heterogeneous catalyst; multicomponent; ZnO-beta zeolite

ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite